The Improvement of Management Model Learning Islamic Education (PAI) Based on Scientific Approach - Muntari, Witi Muntari; Slamet, Achmad; Subagyo, Subagyo (Educational Management, 2018)
Muntari, Witi, 2018. Development of PAI Learning Model Management Based on Scientific Approach